2020
DOI: 10.1055/s-0040-1708558
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Acute Pulmonary Embolism and Determining the Effect on Chronic Cardiopulmonary Complications: The REACH Study

Abstract: Introduction Patients with acute pulmonary embolism (PE) are at risk of developing chronic complications including the post-PE syndrome with reduced cardiopulmonary function and chronic thromboembolism pulmonary hypertension (CTEPH). Risk stratification at PE diagnosis is an important tool in predicting early mortality; however, its use in predicting chronic complications has not been evaluated. Objective This study investigates the effect of initial risk stratification of intermediate risk and stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…This is an important distinction as chronic RVD is more common in those with submassive PE. These results are consistent with a retrospective study of 508 patients from our own centre [ 69 ]. Normotensive patients were stratified into intermediate-risk ( n = 126) and standard-risk ( n = 382) by the presence or absence of RVD, respectively.…”
Section: Long-term Complications After Submassive Pesupporting
confidence: 93%
See 1 more Smart Citation
“…This is an important distinction as chronic RVD is more common in those with submassive PE. These results are consistent with a retrospective study of 508 patients from our own centre [ 69 ]. Normotensive patients were stratified into intermediate-risk ( n = 126) and standard-risk ( n = 382) by the presence or absence of RVD, respectively.…”
Section: Long-term Complications After Submassive Pesupporting
confidence: 93%
“…The high rate of persistent RVD has also been reported in other studies [ 69 , 70 ]. Levinson et al demonstrated RVD in 17% of PE patients at 6 month follow-up [ 70 ].…”
Section: Long-term Complications After Submassive Pesupporting
confidence: 79%
“…Residual defects can be identified in up to 50% of patients when studied using lung perfusion scintigraphy 3–12 months after an acute PE. [ 1 , 2 ] The thromboembolic material is replaced by fibrotic material, develops an endothelial covering and cannot be cleared by anticoagulation or thrombolytic therapy. [ 3 ] Despite the prevalence of residual intravascular material, the development of pulmonary hypertension is uncommon – reported to be <1% in clinical practice, and 2–3% in the prospectively followed Pulmonary Embolism Thrombolysis (PEITHO) study.…”
Section: Pathophysiology Of Chronic Thromboembolic Pulmonary Hypertenmentioning
confidence: 99%
“…The latter is associated with significant morbidity and mortality with a 5-year survival of less than 30%. 19,20 Therefore, it is imperative that acute VTE is promptly diagnosed and appropriately treated. In this section, we briefly discuss recent key developments in the diagnosis and treatment of acute VTE.…”
Section: New Insights In Vte Pathogenesismentioning
confidence: 99%